2016
DOI: 10.3758/s13421-016-0615-x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking as a friend of induction in verbal category learning

Abstract: We conducted an experiment to investigate the influences of interleaved versus blocked presentation of disparate verbal exemplars on the induction of category concepts. The practice schedules of four experimental groups were juxtaposed such that sets of exemplar-category associations were either solved in succession (i.e., blocked), systematically intermixed (i.e., interleaved), or presented with an incremental transition from blocked to interleaved practice. Counter to current trends in the literature, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Although category similarity and category type have both been shown to moderate the efficacy of learning techniques, the interaction between these two factors has received scant empirical or theoretical attention. Several researchers have speculated about the possibility of such an interaction, but have not offered a thorough treatment of the subject (see, e.g., Carvalho & Goldstone, 2015b;Noh et al, 2016;Sorensen & Woltz, 2016;Zulkiply & Burt, 2013a). The purpose of this review was to gather and discuss empirical evidence concerning an interaction between these moderators.…”
Section: Introductionmentioning
confidence: 99%
“…Although category similarity and category type have both been shown to moderate the efficacy of learning techniques, the interaction between these two factors has received scant empirical or theoretical attention. Several researchers have speculated about the possibility of such an interaction, but have not offered a thorough treatment of the subject (see, e.g., Carvalho & Goldstone, 2015b;Noh et al, 2016;Sorensen & Woltz, 2016;Zulkiply & Burt, 2013a). The purpose of this review was to gather and discuss empirical evidence concerning an interaction between these moderators.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that interleaved presentation may be beneficial for inductive learning (Higgins & Ross, 2011;Kang & Pashler, 2012;Kornell & Bjork, 2008;Kornell et al, 2010;Rohrer & Taylor, 2007). However, other studies have found no positive effect of interleaved presentation (Carpenter & Mueller, 2013;Dobson, 2011;Higgins & Ross, 2011;Rau et al, 2010;Sorensen & Woltz, 2016). A recent meta-analysis (Brunmair & Richter, 2019) shed light on these mixed results revealing that interleaving is most effective when learning complex visual stimuli, and when the similarity between the interleaved concepts is high.…”
Section: Blocking and Interleavingmentioning
confidence: 99%
“…It is important to note that the studies reviewed thus far all implemented blocking and interleaving throughout the whole training phase. Sorensen and Woltz (2016) combined blocked and interleaved presentation and reported that better learning of verbal categories in a hybrid condition compared to a condition that employed interleaved presentation alone.…”
mentioning
confidence: 99%
“…The answer may stem from the fact that L2 learning of Spanish verb conjugation skills is a multi-stage process involving different cognitive skills at different stages (e.g., learning explicit rules vs. recalling and applying those rules; for an analogous example see Kole & Healy, 2013). For relatively complex skills that involve a transition from knowledge to application (e.g., Anderson & Krathwohl, 2001;Bloom, 1956Bloom, , 1984, it may be the case that interleaving that is implemented too early impairs the acquisition of basic knowledge (possibly if explicit rules are involved, as suggested by Sorensen & Woltz, 2016), thus affecting learners' ability to later apply that knowledge. More research is needed to scrutinize that possibility across foreign language and other materials (e.g., other subdomains of language learning may also require the initial acquisition of basic knowledge before interleaving and other learning interventions are effective).…”
Section: Hybrid Interleaving Schedulesmentioning
confidence: 99%
“…The results of Experiments 3 and 4 also stand in contrast to prior work on hybrid schedules that involved different designs and yielded divergent results. Specifically, the hybrid schedules used in Sorensen and Woltz (2016) and Yan et al (2017; Experiments 1 and 2) did not involve multiple training phases on component tasks as in the present experiments. Rather, a single task type was first learned under blocked, and then interleaved, conditions.…”
Section: Hybrid Interleaving Schedulesmentioning
confidence: 99%